Laser exposure induced alteration of WS2 monolayers in the presence of ambient moisture. (23rd October 2017) - Atkin, P; Lau, D W M; Zhang, Q; Zheng, C; Berean, K J; Field, M R; Ou, J Z; Cole, I S; Daeneke, T; Kalantar-Zadeh, K
Abstract: Photoluminescence (PL) emergence in monolayer transition metal dichalcogenides (TMDs) such as WS2, has been one of the key attractions of such materials. However, there have been many observational contradictions in PL measurements presented in the past literature. This work addresses such issues. Firstly, the observational changes of the flakes' PL patterns under exposure to various intensities of radiant exposure via laser sources are presented. These experiments show that these changes are a function of radiant exposure. Interestingly, it is observed that PL loss is accompanied by a change of the profile height for WS2 monolayers. In order to explore the fundamental mechanism for PL and height variations, laser irradiation was applied to monolayer WS2 flakes with varying radiant exposure to obtain PL maps, under the absence and presence of oxygen, H2 O and nitrogen molecules in the atmosphere. It was seen that, after relatively high radiant exposure (>15 mJ µ m −2 ), the PL pattern loss occurs only in the presence of atmospheric H2 O molecules (45% humidity) and is also accompanied by an increase in height. Compositional analysis determined that this height increase was due to the substitution of surface S atoms with sulphate groups. This discovery represents an important step forward in understanding the necessary precautions when investigating optical properties of 2D TMDs in atmospheric conditions, and highlights the need for precise evaluation of the thresholds for radiant exposure at which specific reactions begin to occur. This knowledge is crucial for efficient and effective control of ambient operating conditions for optical characterisation of monolayer WS2 and TMDs in general.